Denaturation Kinetics of Whey Protein Isolate Solutions and Fouling Mass Distribution in a Plate Heat Exchanger - Marwa Khaldi; Gilles Ronse; Christophe André; Pascal Blanpain-Avet; Laurent Bouvier; Thierry Six; Saloua Bornaz; Thomas Croguennec; Romain Jeantet; Guillaume Delaplace (International Journal of Chemical Engineering)
Few investigations have attempted to connect the mechanism of dairy fouling to the chemical reaction of denaturation (unfolding and aggregation) occurring in the bulk. The objective of this study is to contribute to this aspect in order to propose innovative controls to limit fouling deposit formation. Experimental investigations have been carried out to observe the relationship between the deposit mass distribution generated in plate heat exchangers (PHE) by a whey protein isolate (WPI) mainly composed of β-lactoglobulin (β-Lg) and the ratio between the unfolding and aggregation rate constants. Experiments using a PHE were carried out at a pilot scale to identify the deposit distribution of a model fouling solution with different calcium contents. In parallel, laboratory experiments were performed to determine the unfolding/aggregation rate constants. Data analysis showed that (i) β-Lg denaturation is highly dependent on the calcium content, (ii) for each fouling solution, irrespective of the imposed temperature profile, the deposit mass in each channel and the ratio between the unfolding and aggregation rate constants seem to be well correlated. This study demonstrates that both the knowledge of the thermal profile and the β-Lg denaturation rate constants are required in order to predict accurately the deposit distribution along the PHE.